Prevalence of gingivitis and correlation between frequency of brushing and gingivitis in 3- to 15-year-old school children in rural parts of Barabanki District, Uttar Pradesh, India - Vertika Gupta; Prerna Vishwanath; Nalini Tripathi (Wolters Kluwer Medknow Publications, 2022)
Background: In India, the majority population lives in rural areas where there is less awareness on the maintenance of oral health. At the rural level, less work has been done among children to determine the incidence of gingival disease and its relation to the cleaning rate. Hence, it is necessary to evaluate the prevalence of gingivitis among these masses. Aims and Objectives: The goal of the study was to determine the prevalence of gingivitis and its relation to the frequency of tooth brushing among school-going children between 3 and 15 years of age group in rural areas of Barabanki district, India. Materials and Methods: The study was done on a sample size of 1200 school-going children, in which 611 boys and 589 girls are there, from rural schools of Barabanki. The sample consisted of four age groups of children from 3 to 5 years, 6-9 years, 10-12 years, and 13-15 years of age. Gingival Index given by Loe and Silness was used to determine the severity of gingivitis. The data were evaluated using the Chi-square test. Results: The overall prevalence of gingivitis obtained was 86.17% and it was highly significant in relation to age groups. On comparing the frequency of brushing and gingivitis in all age groups it was revealed that twice daily brushing was significantly related to healthy gingiva. Conclusions: The study revealed a high prevalence rate of gingivitis among children in these age groups indicating oral health program is highly recommended for both parents and school children in rural areas to maintain oral hygiene.